Estudo da incidência de falhas visando a melhoria da qualidade dos sistemas prediais hidráulicos e sanitários - Conceição, Alessandro Pucci da (2007)
Several factors have been demanding from the building enterprises to search for better quality in their gerencial organization, methods and construtive techniques have been used, like the cost reductions for their permanency in the market, trough the rationalize of their process and the legal aspects of the Consumer Defense Code, among others. For that a building execute the requisits related to the aspects of performance from their functions during their utilization, is necessary during their life, to use a pre-determinated plan of maintenance, that must be seen as another stage of the constructions process, as well as the conception stage, project and building execution. The construction building patology study, is a fundamental instrument to be possible to identify and to understand the falilure incident on performance during the utilization of the buildings components.The present production tryed to show the performance requirements in two medium to high standard entrerprise buildings, that has norms and procedure of quality control. Information were utilized from the project stage until the execution and post-occupancy stage of the enterprise, with purpose to localize possibles pathologies in fase of utilization, and track them with their history of projects or with sistem and construtive procedure. Based on information obtained in this study, the results were realized with the purpose of systemaze the information to elaborate the grafics and other tools to enable a better comprehension of problems detected.Through the results obtained, together with the project studied and construtives methods adopted trought the building enterprise, were realized the Identification and the caracterization of the main pathology . The objective of this production is to provide information to searches in this pathologies in the Hydraulics and Sanitary buildings Systems and buildings enterprises to aim to aid on control and syatematizing the necessaries maintenance, to prevent the same problems in future buildings executed by the enterprises and the executer of theses systems.